Aplicação de polímeros na construção de nanomateriais híbridos auto-organizados - Scaravelli, Roberta Cristina Barros (2013)
In this work the single-step/single-phase synthesis of hybrid organic-inorganic core-shell gold nanoparticles (AuNPs), facilitated by amino-functionalized amphiphilic block copolymers that simultaneously play the roles of reductant and stabilizer, was investigated in this study. Experiments were devised with emphasis on the pH-responsive poly(ethylene oxide)-b-poly(2,3-dihydroxypropyl methacrylate)-b-poly[2-(diisopropylamino)ethyl methacrylate] triblock copolymer, which allows direct chemical cross-linking of the micellar structures to be performed. The polymer structure-reactivity relationship associated with the AuNP formation was established using a set of six structurally related macromolecules. AuNP formation was dependent on the aqueous dissociation equilibrium involving tertiary amino groups, the Au(III) speciation, and electrochemical redox potentials. The effects of these parameters on the synthesis of AuNPs change as the solution pH is increased from pH 3.5 (molecularly dissolved polymer chains; no AuNP formation) to 6.8 or higher (polymer chains self-assembled into spherical micelles; stable gold sols are produced), and Au(III) reduction potentials shift toward the cathodic region whilst the oxidation potential of deprotonated amino groups decreases. Sigmoidal nanoparticle growth kinetics was observed in all cases after a characteristic induction period. Stable, well-defined, uniform polymer-coated gold colloids with localized surface plasmon resonance centered at 530 nm can be conveniently produced in one-pot, two-reactant, no work-up reactions when the stoichiometry is [N]/[Au] = 3.5 - 25.0.